Faire la Difference Par La Video
Faire la Difference Par La Video is the French langyage version of VIDEO FOR CHANGE, the second training video produced by WITNESS. Using footage shot by human rights activists from around the world, WITNESS VIDEO FOR CHANGE illustrates the various strategic ways video and internet technology can be used to further human rights advocacy efforts. The video is accompanied by a written manual used to train human rights activists in video documentation.